Integration of Socio-Agroecosystem in the Implementation of Semi-Autonomous Hand Tractors in Wetlands: Efforts to Empower Women and the Elderly Towards Sustainable Agriculture - Saputri, Dellah Tian; Rejo, Amin; Adhiguna, Rizky Tirta (Program Pascasarjana Universitas Sriwijaya, 2025)
Abstract: Pelabuhan Dalam Village, Ogan Ilir, is a swamp–lowland agricultural area dominated by rice cultivation. Challenges such as the decline in productive labor, the use of conventional tractors that cause soil compaction, and the low participation of women and the elderly have led to socio-economic and ecological problems. This study integrates a socio-agroecosystem approach through the implementation of semi-autonomous hand tractors to improve technical efficiency and community empowerment. The results show a 31% increase in work efficiency, a 17% reduction in fuel consumption, and a 21% decrease in soil compaction. The participation of women and the elderly also increased, accompanied by a 16% rise in household income per planting season. This integration has proven effective in promoting socio-economic welfare and the sustainability of wetland agriculture in South Sumatra.